Pelvic triton malignant tumor: case report - Limaylla Vega, Himerón Perfecto (2014)
We report the case of a 29 year-old woman complaining of pain in right buttock and leg. She suffered of von Recklinghausen disease and developed rapidly growing retroperitoneal pelvic tumors. At laparotomy the tumors were attached to the obturator foramen and the iliac wing. The larger and fast growing right side tumor compatible with malignant triton tumor, and the left sided neurofibroma were removed.